Global monitoring report 2011 : improving the odds of achieving the MDGs : heterogeneity, gaps, and challenges. - World Bank.; International Monetary Fund.; International Bank for Reconstruction and Development (Washington, D.C. : International Bank for Reconstruction and Development, the World Bank, 2011)
The book takes a closer look at the diversity of country progress, presents the challenges that remain, and assesses the role of growth, policy reforms, trade, and donor policies in meeting the MDGs.
Prepared jointly by The World Bank and the International Monetary Fund.
Includes bibliographical references.
rua 19/07/13, ijb 21/02/2019
Loans
Keywords: Economic development; Economic development; Economic policy; Economic policy